Editorial: Accumulating Evidence for the Benefit of Micronutrients for Children With Attention-Deficit/Hyperactivity Disorder - Stevenson, Jim (Journal of the American Academy of Child and Adolescent Psychiatry, 2022)
The first paper indicating that a central nervous system stimulant (amphetamine) could be beneficial for children with attention-deficit/hyperactivity disorder (ADHD)−like behavioral symptoms appeared in 1937.1 Over the subsequent 80 years, a range of additional stimulant (methylphenidate) and nonstimulant (atomoxetine, clonidine, guanfacine, and, most recently, viloxazine) drugs have been approved to treat children and adolescents with ADHD. These drug treatments have been the subject of a large number of randomized controlled trails (RCTs). A network meta-analysis found that using clinician ratings, amphetamine, methylphenidate, and atomoxetine were all significantly superior to a placebo.2 These findings suggest that in the short-term at least, these treatments are effective—data are sparse on the efficacy of longer-term drug treatment. However, there are longstanding worries about the use of such drug treatments with children. In particular there are concerns over possible adverse impact on growth. There are also less tangible, but important, concerns of parents as the whether it is appropriate to subject their children to the modification of behavior by drugs.3 For these reasons, there is an urgent need to develop nonpharmacological treatments for children and adolescents with ADHD. One such nonpharmacological treatment is dietary supplementation with micronutrients. In this issue of the Journal, Johnstone et al.4 present a study of micronutrients showing that, under the stringent conditions of an RCT, micronutrients substantially benefit the well-being of young people with ADHD and irritability (risk ratio [RR] = 2.97; 97.5% CI = 1.50−5.90).